C-reactive protein levels could be a prognosis predictor of prostate cancer: A meta-analysis - Zhou, Kechong; Li, Chao; Chen, Tao; Zhang, Xuejun; Ma, Baoluo (Frontiers in Endocrinology, 2023)
Background: The relationship between the C reactive protein (CRP) and prognosis in prostate cancer (PCa) Has been widely discussed over the past few years, but remains controversial. Material and methods: In our meta-analysis, 16 reliable studies were searched in PubMed, Embase and Cochrane Library databases. Otherwise, We have successfully registered on the INPLASY. We also performed random and fixed effects models to evaluate the hazard ratio (HR) and 95% confidence interval (CI) respectively. Result: The result of our meta-analysis shows that the elevated CRP level were both related with worse overall survival (OS) (HR = 1.752, 95%CI = 1.304-2.355, P = 0.000), cancer-specific survival (CSS) (HR = 1.663, 95%CI = 1.064-2.6, P = 0.026) and progression free survival (PFS) (HR = 1.663, 95%CI = 1.064-2.6, P = 0.026) of PCa patients. There were significant heterogeneity, so we performed a subgroup analysis by the staging of the disease and found the same result. Furthermore, the heterogeneity were also reduce and no statistical significance. Conclusion: Our study shows that the level of CRP could reflect the prognosis of prostate cancer patients. We find that PCa patients with high levels of CRP often have worse OS, CSS and PFS although the stage of the patients are different. More researches are needed to verify this idea.